2003
DOI: 10.1002/uog.920
|View full text |Cite
|
Sign up to set email alerts
|

Results of endosonographic imaging of the anal sphincter 2–7 days after primary repair of third‐ or fourth‐degree obstetric sphincter tears

Abstract: Objectives To describe the endosonographic image of the anal sphincter 2-7 days after delivery in women who had undergone a primary repair of an obstetric sphincter tear. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 26 publications
2
67
1
1
Order By: Relevance
“…The use of ultrasound for evaluation of the anal sphincter soon after surgical repair has been discussed previously in the literature, using either the transperineal approach or the endoanal approach, with the known benefits and disadvantages of each4, 5, 15, 16. A recent study by Olsen et al 17 showed that the endoanal and transvaginal approaches visualized the anatomy of the posterior compartment, and that the transvaginal approach allowed visualization of the anal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound for evaluation of the anal sphincter soon after surgical repair has been discussed previously in the literature, using either the transperineal approach or the endoanal approach, with the known benefits and disadvantages of each4, 5, 15, 16. A recent study by Olsen et al 17 showed that the endoanal and transvaginal approaches visualized the anatomy of the posterior compartment, and that the transvaginal approach allowed visualization of the anal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…2A and B) of any IAS and EAS defect, the Starck classification assigns a score from 0 to 16. The damage is classified as small (score of 1-4), moderate (score of 5-7), or large (score of 8-16) [11]. On 3D-EAUS, scar tissue appears as endosonographic areas of mixed echogenicity, whereas atrophy is seen as a thin and poorly defined sphincter with heterogeneous increased echogenicity [12].…”
Section: Methodsmentioning
confidence: 99%
“…Sultan et al reported that following a repair in the labour ward 65% had persisting defects on an endo-anal ultrasound scanning [29]. A study by Starck et al showed that when an endo-anal ultrasound scan was carried out 2-7 days after a primary repair of third or fourth degree obstetric injuries, 90% had persisting defects [30]. These authors have further studied the outcome of tears in a report in 2006.…”
Section: Classification Of Tearsmentioning
confidence: 93%